Differentiation of organic and non‐organic winter wheat cultivars from a controlled field trial by crystallization patterns. (6th August 2014) - Kahl, Johannes; Busscher, Nicolaas; Mergardt, Gaby; Mäder, Paul; Torp, Torfinn; Ploeger, Angelika
Abstract BACKGROUND There is a need for authentication tools in order to verify the existing certification system. Recently, markers for analytical authentication of organic products were evaluated. Herein, crystallization with additives was described as an interesting fingerprint approach which needs further evidence, based on a standardized method and well‐documented sample origin. RESULTS The fingerprint of wheat cultivars from a controlled field trial is generated from structure analysis variables of crystal patterns. Method performance was tested on factors such as crystallization chamber, day of experiment and region of interest of the patterns. Two different organic treatments and two different treatments of the non‐organic regime can be grouped together in each of three consecutive seasons. When the k‐nearest‐neighbor classification method was applied, approximately 84% of Runal samples and 95% of Titlis samples were classified correctly into organic and non‐organic origin using cross‐validation. CONCLUSION Crystallization with additive offers an interesting complementary fingerprint method for organic wheat samples. When the method is applied to winter wheat from the DOK trial, organic and non‐organic treated samples can be differentiated significantly based on pattern recognition. Therefore crystallization with additives seems to be a promising tool in organic wheat authentication. © 2014 Society of Chemical Industry